Progressive Failure Analysis for Design and Construction of Suspended Cabins. Issue 1 (2nd January 2018) - Lin, Feng; Qiu, Lu; Pang, Yanfeng
Abstract: The Music and Culture Center (MCC) building, located in Shanghai, is a unique structure with three cabins suspended under the main structure by steel cables. A specific design approach involving progressive failure analysis was essential due to the structural characteristics such as less redundancy and safety sensitivity. An analysis strategy based on finite element method was adopted with consideration of material strength, load combinations, failure criteria for structural elements and specific failure criteria for the building regarding the incline of the cabin floor. The results indicated that progressive failure did not happen after the removal of individual cables. The presented design approach and construction method are both general and significant for suspended structures.